PREVALENCE AND CLINICAL CHARACTERISTICS OF ALLERGIC RHINITIS AMONG ASTHMATIC PATIENTS IN THE EMERGENCY DEPARTMENT OF A BHAYANGKARA BRIMOB HOSPITAL IN INDONESIA: PREVALENSI DAN KARAKTERISTIK KLINIS RINITIS ALERGI PADA PASIEN ASMA DI INSTALASI GAWAT DARURAT RUMAH SAKIT BHAYANGKARA BRIMOB DI INDONESIA - Winugroho, Mohammad Lukmanul Hakim; Kemuning, Asri Ragil; Rusmajati, Jetty; Desdiani (Faculty of Medicine Universitas Islam Sumatera Utara, 2025)
Introduction: Asthma and allergic rhinitis frequently coexist. Objective: This study aims to characterize adult asthma patients who visited the emergency department (ED) and had allergic rhinitis between June 2023 and December 2024 at Bhayangkara Hospital, Depok City, West Java. Methods: This retrospective study analyzed 144 asthma patients who visited the ED during the specified period. The cohort included 89 females and 55 males. Diagnoses of bronchial Asthma and allergic rhinitis were confirmed through clinical history and physical examination by the attending physician, and all data is obtained from the patient's medical records. Results: Among the study population, 66.66% had coexisting asthma and allergic rhinitis. The majority were female and aged between 18 and 44 years. Chest X-rays revealed no significant abnormalities. Asthma prevalence was higher in females (61.8%) than males (38.19%), with a mean age of 32.53 years. A history of atopy, encompassing conditions like eczema, food allergies, and eye inflammation, was prevalent among 46.52% of patients. Smoking habits varied, with 74.3% being ex-smokers or non-smokers, while 25.69% were current smokers. Passive smoke exposure was noted in 37.5%, and 7.63% had exposure to biomass fuel. About 88.19% of emergency patients visits were classified as moderate asthma attacks, with 66.93% of these patients also having allergic rhinitis. Severe asthma attacks occurred in 11.8% of cases, with 58.82% of these patients also suffering from allergic rhinitis. Conclusions: The high prevalence of allergic rhinitis among asthma patients emphasizes the necessity of early diagnosis and good management to optimize patient outcomes.